Sistema de gestión de contratos y firmas electrónicas para F1 Top Point (2022)
In the last years of the pandemic, the creation of contracts at the F1 Top Point company became a time-consuming task, due to the significant increase in the number of documents to be prepared, which made the work of the administrative officer in the contracting area difficult. Through the implementation of the mobile application for the management of contracts and electronic signatures, which allows signing contracts efficiently and without any setback, associated with the work of generating and signing physical documents, the company can optimize the administrative processes of significantly and speed up the work of the contracting area.